2019
DOI: 10.4028/www.scientific.net/jnanor.59.1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gold Nanoparticles in Sonosensitization of Human Cervical Carcinoma Cell Line under Ultrasound Irradiation: An <i>In Vitro</i> Study

Abstract: Abstract:Purpose: The objective of this investigation was to evaluate the combined effects of ultrasound irradiation as a non-invasive and non-ionizing radiation with gold nanoparticles as ultrasound sensitizers on the HeLa cells.Materials and Methods: First, Gold nanoparticles (GNPs) were prepared, and the characterizations of nanoparticles were analyzed using TEM and UV-vis. Different concentrations of nanoparticles (0.2, 1, 5, 25 and 50 μg/ml) were used. Then, cytotoxicity of the GNPs was studied on HeLa ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Ultrasound is one of the non-invasive modalities for the treatment of some cancers (19) , which is defined as mechanical vibration produced via sound waves with a frequency of more than 20 kHz [20]. It has been reported that the effective therapeutic frequency of ultrasound is in the range of 0.8 to 3 MHz (21,22) .Ultrasound waves by different thermal, mechanical, and micro-bubbles cavitation can play vital roles in cancer treatments (23)(24)(25) . Physically, the ultrasound waves could may increase the temperature of the cell microenvironment by the generation of thermal energy (22,26,27) and also bubble (28) .…”
mentioning
confidence: 99%
“…Ultrasound is one of the non-invasive modalities for the treatment of some cancers (19) , which is defined as mechanical vibration produced via sound waves with a frequency of more than 20 kHz [20]. It has been reported that the effective therapeutic frequency of ultrasound is in the range of 0.8 to 3 MHz (21,22) .Ultrasound waves by different thermal, mechanical, and micro-bubbles cavitation can play vital roles in cancer treatments (23)(24)(25) . Physically, the ultrasound waves could may increase the temperature of the cell microenvironment by the generation of thermal energy (22,26,27) and also bubble (28) .…”
mentioning
confidence: 99%